Obesity-induced mesenteric PVAT remodelling is sexually dimorphic, but not driven by ovarian hormones - Lisa Ivatt; Mhairi Paul; Allende Miguelez-Crespo; Patrick W. F. Hadoke; Matthew A. Bailey; Ruth A. Morgan; Mark Nixon (Cardiovascular Diabetology)
Abstract Background Obesity, a major risk factor for cardiovascular disease (CVD), is associated with hypertension and vascular dysfunction. Perivascular adipose tissue (PVAT), a metabolically active tissue surrounding blood vessels, plays a key role in regulating vascular tone. In obesity, PVAT becomes dysregulated which may contribute to vascular dysfunction; how sex impacts the remodelling of PVAT and thus the altered vascular contractility during obesity is unclear. Objective To investigate sex-specific PVAT dysregulation in the setting of obesity as a potential driver of sex differences in vascular pathologies and CVD risk. Methods Adult male and female C57Bl/6J mice were fed an obesogenic high-fat diet (HFD) or regular chow for 16 weeks. Mesenteric PVAT (mPVAT) was isolated for RNA-sequencing and histological analysis, and mesenteric arteries were isolated for assessment of vascular function by wire myography. In a separate study, female mice were subjected to bilateral ovariectomy prior to dietary intervention to determine the contribution of ovarian hormones to PVAT dysregulation. Results Transcriptomic analysis of mPVAT revealed sexually dimorphic responses to HFD, with upregulation of extracellular matrix (ECM) remodelling pathways in male but not female mice. Histological and RT-qPCR approaches demonstrated increased collagen deposition and ECM remodelling in mPVAT from obese male compared with obese female mice. Assessment of vascular function in mesenteric arteries -/+ PVAT revealed that in obesity, mPVAT impaired endothelium-mediated vasodilation in male but not female mice. Ovariectomy of female mice prior to HFD administration did not alter ECM transcript expression or collagen deposition in mPVAT compared to sham-operated female mice. Conclusions Obesity induces sex-specific molecular remodelling in mPVAT, with male mice exhibiting unique upregulation of ECM pathways and increased collagen deposition compared to females. Moreover, the relative protection of female mice from obesity-induced mPVAT dysregulation is not mediated by ovarian hormones. These data highlight a potential sex-specific mechanistic link between mPVAT and mesenteric artery dysfunction in obesity, and provides crucial insights for future development of treatment strategies that consider the unique cardiovascular risks in men and women. Graphical abstract